Creating one problem to try and fix another: the saga of ischemic preconditioning. Issue 6 (15th September 2013) - Caplan, Louis R.
<x xml:space="preserve">Abstract</x> I plan in this editorial to place ischemic preconditioning into a historical context, to critique its potential benefits, risks, and limitations, and to try to look ahead at its future applications if any. <boxed-text content-type="graphic" id="brb3170-blkfxd-0101" position="anchor" orientation="portrait"> </boxed-text>